Establishment of TSH β real‐time monitoring system in mammalian photoperiodism. (12th June 2013) - Tsujino, Kaori; Narumi, Ryohei; Masumoto, Koh‐hei; Susaki, Etsuo A.; Shinohara, Yuta; Abe, Takaya; Iigo, Masayuki; Wada, Atsushi; Nagano, Mamoru; Shigeyoshi, Yasufumi; Ueda, Hiroki R.
<x xml:space="preserve">Abstract</x> Organisms have seasonal physiological changes in response to day length. Long‐day stimulation induces thyroid‐stimulating hormone beta subunit (TSHβ) in the pars tuberalis (PT), which mediates photoperiodic reactions like day‐length measurement and physiological adaptation. However, the mechanism of TSHβ induction for day‐length measurement is largely unknown. To screen candidate upstream molecules of TSHβ, which convey light information to the PT, we generated Luciferase knock‐in mice, which quantitatively report the dynamics of TSHβ expression. We cultured brain slices containing the PT region from adult and neonatal mice and measured the bioluminescence activities from each slice over several days. A decrease in the bioluminescence activities was observed after melatonin treatment in adult and neonatal slices. These observations indicate that the experimental system possesses responsiveness of the TSHβ expression to melatonin. Thus, we concluded that our experimental system monitors TSHβ expression dynamics in response to external stimuli.